1997
DOI: 10.1111/j.1751-1097.1997.tb01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Effect of Magnetite Particles on the Dynamics of Photogenerated Free Radicals

Abstract: Abstract— Polymeric particles of about 1 u.m in diameter and containing around 40% magnetite have a dramatic influence on the dynamics of triplet radical pair reactions occurring in micelles in their vicinity. The effect has been monitored with laser flash photolysis techniques and results in a decrease of the number of radicals that separate from their geminate partner and an acceleration of radical pair geminate reactions. The effect involves remote interactions because the solution contains ca 1011micelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…It has also been pointed out that trace amounts of magnetite may be ubiquitous and that a single 100-nm magnetite crystal exposed to a 60 Hz, 0.1 mT magnetic field could absorb sufficient energy to supercede thermal background noise several fold (Kobayashi et al 1995). Magnetite particles can have dramatic effects on the dynamics of photogenerated free radicals (Scaiano et al 1997). Particularly in the context of the radical-pair mechanism (see below) it is thus pertinent to reckon with the modulating effect of magnetites if present.…”
Section: Ferrimagnetismmentioning
confidence: 98%
“…It has also been pointed out that trace amounts of magnetite may be ubiquitous and that a single 100-nm magnetite crystal exposed to a 60 Hz, 0.1 mT magnetic field could absorb sufficient energy to supercede thermal background noise several fold (Kobayashi et al 1995). Magnetite particles can have dramatic effects on the dynamics of photogenerated free radicals (Scaiano et al 1997). Particularly in the context of the radical-pair mechanism (see below) it is thus pertinent to reckon with the modulating effect of magnetites if present.…”
Section: Ferrimagnetismmentioning
confidence: 98%
“…However, in a recent SQUID magnetometry study, Hautot et al [67] reported elevated levels of biogenic magnetite in female AD subjects compared to both male and female controls. The significance of these findings is that magnetite provides a potential source of ferrous iron, which is available for oxidation and participation in Fenton chemistry (the oxidation product of magnetite, maghemite-cFe 2 O 3 , has also been found in AD tissue) and may potentiate free radical formation in AD tissue via triplet state stabilization [68][69][70][71].…”
Section: Iron-containing Compounds Related To Alzheimer Diseasementioning
confidence: 98%
“…Magnetite is a magnetic (ferrimagnetic) iron oxide with alternating lattices of Fe 2 1 and Fe 3 1 ions, which is capable of producing free radicals via the Fenton reaction or via triplet state stabilization (Kirschvink 1992;Scaiano et al 1997;Chignell & Sik 1998). Recent experiments have also demonstrated that iron-oxygen complexes may be even more effective catalysts for free-radical damage in brain tissue than the Fenton reaction (Schafer et al 2000), so the potential deleterious effect of magnetite is possibly even more significant.…”
Section: Introductionmentioning
confidence: 95%